2015
DOI: 10.1097/pas.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Branched Chain In Situ Hybridization for Albumin as a Marker of Hepatocellular Differentiation

Abstract: Introduction Albumin, widely recognized as a highly sensitive and specific marker of hepatocellular carcinoma (HCC) is currently unavailable in the diagnostic laboratory because of the lack of a robust platform. In a prior study we detected albumin mRNA in the majority of intrahepatic cholangiocarcinomas using a novel branched chain RNA in situ hybridization (ISH) platform. We now explore the utility of albumin ISH as a marker of hepatocellular differentiation in hepatocellular carcinomas, and compare its sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 20 publications
2
38
1
Order By: Relevance
“…Hooper et al showed that HPC2 expression was observed in 80% of PDACs, and 32% of ICAs, while N-cadherin antibody stained 27% of the PDAC resections versus 58% of the ICA resections [35]. Recently, a novel technology using branched DNA-enhanced albumin RNA in situ hybridization was reported to distinguish hepatocellular carcinoma and ICA from metastatic PDAC [36, 37]. Although promising, none of these previous studies have found their way into the current routine clinical practice due to their low specificity or sensitivity, or technical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Hooper et al showed that HPC2 expression was observed in 80% of PDACs, and 32% of ICAs, while N-cadherin antibody stained 27% of the PDAC resections versus 58% of the ICA resections [35]. Recently, a novel technology using branched DNA-enhanced albumin RNA in situ hybridization was reported to distinguish hepatocellular carcinoma and ICA from metastatic PDAC [36, 37]. Although promising, none of these previous studies have found their way into the current routine clinical practice due to their low specificity or sensitivity, or technical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is a protein synthesized by hepatocytes, and has recently been shown to be a highly sensitive and specific marker for hepatocellular differentiation when detected by branched‐chain in‐situ hybridization (bISH) . In a recent study, we showed that >95% of intrahepatic cholangiocarcinomas stain positively for albumin, suggesting that intrahepatic cholangiocarcinomas and hepatocellular carcinomas arise from a common progenitor cell.…”
Section: Introductionmentioning
confidence: 97%
“…The IgG4 probe is isotype‐specific, whereas the IgG probe targets RNA sequences to all IgG subclasses. Additional details are presented in a prior publication from this institution …”
Section: Methodsmentioning
confidence: 99%